The technique of measuring thrombin generation with fluorescent substrates: 4. The H-transform, a mathematical procedure to obtain thrombin concentrations without external calibration - Hemker, Coen H.; Hemker, Pieter W.; Dieri, Raed Al (Thrombosis and Haemostasis, 2009)
In fluorogenic thrombin generation (TG) experiments, thrombin concentrations cannot be easily calculated from the rate of the fluorescent signal increase, because the calibration coefficient increases during the experiment, due to substrate consumption and quenching of the fluorescent signal by the product. Continuous, external calibration via an in a parallel sample therefore was hitherto required for an accurate calculation of the TG curve. A technique is presented that allows mathematical transformation of experimental fluorescence intensities into “ideal” data, i.e. in the data that would have been obtained if substrate consumption and quenching by the product would not play a role. The method applies to fluorescence intensities up to 90% of the maximal fluorescent signal corresponding to total substrate conversion and thereby covers the entire region of interest encountered in practice. The first derivative of the transformed signal can then be converted into thrombin concentrations via a conventional, fixed calibration factor. This calibration factor can be obtained from a separate experiment but also by measuring the amidolytic activity of the α2macroglobulin-thrombin complex present in the reaction mixture (“serum”) after thrombin generation is over. This method halves the amount of sample required per experiment.
Keywords: Thrombin generation; fluorogenic methods; calibration